x-2*y=3 a*x+y=2

1 уравнение:
2 уравнение:
3 уравнение:
4 уравнение:
5 уравнение:
6 уравнение:
7 уравнение:
8 уравнение:
9 уравнение:
10 уравнение:
11 уравнение:
12 уравнение:
13 уравнение:
14 уравнение:
15 уравнение:
16 уравнение:
17 уравнение:
18 уравнение:
19 уравнение:
20 уравнение:
21 уравнение:
22 уравнение:
23 уравнение:
24 уравнение:
25 уравнение:
26 уравнение:
27 уравнение:
28 уравнение:
29 уравнение:
30 уравнение:
31 уравнение:
32 уравнение:
33 уравнение:
34 уравнение:
35 уравнение:
36 уравнение:
37 уравнение:
38 уравнение:
39 уравнение:
40 уравнение:
41 уравнение:
42 уравнение:
43 уравнение:
44 уравнение:
45 уравнение:
46 уравнение:
47 уравнение:
48 уравнение:
49 уравнение:
50 уравнение:
51 уравнение:
52 уравнение:

Решение

Вы ввели
[LaTeX]
x - 2*y = 3
$$x - 2 y = 3$$
a*x + y = 2
$$a x + y = 2$$
Быстрый ответ
[LaTeX]
$$x_{1} = 2 y + 3$$
=
$$2 y + 3$$
=
3 + 2*y

$$a_{1} = - \frac{y - 2}{2 y + 3}$$
=
$$\frac{- y + 2}{2 y + 3}$$
=
-(-2 + y)/(3 + 2*y)